Analisis Peran Tari Dalam Mengembangkan Keterampilan Sosial Anak Di TK Anline - Lubis, Hilda Zahra; Roaina, Lia; Lubis, Nur Asiah; Amarisa, Yassinta (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This research aims to analyze the role of dance in developing children's social skills at Anline Kindergarten. Social skills are an important component in early childhood development which includes the ability to interact, communicate, work together and manage emotions. The method used in this research was observation and interviews with teachers at Anline Kindergarten. The research results show that dance activities significantly help children improve verbal and non-verbal communication skills, build self-confidence, and facilitate positive social interactions among peers. In addition, dance also contributes to the development of empathy and appreciation for individual and cultural differences. The implementation of dance programs in kindergarten has proven effective in creating an inclusive learning environment and supporting children's holistic social development. This research suggests that dance activities should be made an integral part of the early childhood education curriculum to support the development of better social skills.